Analisis Pemasaran dan Nilai Tambah Pala di Kecamatan Tapak Tuan Kabupaten Aceh Selatan - Mayhilda Nitami; Anna Fariyanti; Ratna Winandi Asmarantaka (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2023)
Based on Ministry of Agriculture data (2019), nutmeg is one of Indonesia's led commodities that have a high economic value which is focused on exporting orientation. This study aims to analyze the marketing efficiency level of nutmeg, and the added value of processed nutmeg products for home industries in Tapak Tuan District, South Aceh Regency. The method used to calculate marketing margin value, farmer's share value, R / C ratio. Meanwhile, the value-added analysis used the Hayami table. The analysis result showed that the nutmeg marketing system in Tapak Tuan District was relatively efficient. The calculating result of the equivalent estimate for the percentage value of the margin was 31.77%, the farmer's share was 68.23%, and the r / c ratio was 2.18. Channel 4 was relatively more efficient compared to other channels with sales volumes of 117.5 kg (type B) and 2.82 kg (mace). In nutmeg value-added processing activities, Permai’s home industry for flower-shaped cake obtained a value-added ratio of 53% and stick-shaped cake at 32%. Finally, Rovan's home industry for flower-shaped cake obtained a ratio of 62%, stick-shaped cake 49.5%, and nutmeg syrup 17%.